Model to support the evaluation of the impact of the use and management of the soil on the water balance - doi: 10.4025/actasciagron.v34i4.14733 - Mello, Eloy Lemos de; Pruski, Fernando Falco; Bertol, Ildegardis; Costa, Lucas Mucida; Menezes, Gleiph Ghiotto; Rodrigues, Nívia Carla (Acta Scientiarum. Agronomy, 2012)
The purpose of this work was to develop a hydrological model for the simulation of the water balance in agricultural areas. The model uses a double exponential equation to represent the rainfall profile and uses the Green-Ampt-Mein-Larson equation to estimate the soil water infiltration rate. To evaluate the model, monthly and yearly rainfall and runoff data were obtained from four experimental plots located at the State University of Santa Catarina, UDESC, in the period from 2003 to 2008. The four treatments were bare soil (BS), conventional tillage (CT), minimum tillage (MT) and no-tillage (NT). The simulation was carried out using two synthetic rainfall series, one adjusted on a monthly basis (SAMB) and the other adjusted on a daily basis (SADB). The parameters for the Green-Amp equation modified by Mein-Larson (GAML) were adjusted, and the best combination was found to be the replacement of the saturated hydraulic conductivity (K) by the constant infiltration rate (fc) and the estimation of the wetting front head pressure as a function of the hydraulic conductivity in the saturation zone (ψ(Kw)). There was not a significant difference between the observed annual mean runoff and the annual mean runoff estimated by the model.